1868. Characterization of COVID-19 Symptoms and Outcomes by Variant Period in the North Carolina COVID-19 Community Research Partnership (NC-CCRP). (15th December 2022) - DeWitt, Michael E; Edelstein, Sharon; Tjaden, Ashley H; Herrington, David M; Schieffelin, John; Gibbs, Michael A; Weintraub, William; Sanders, John W
Abstract: Background: We characterize the evolution of symptoms in those with self-reported SARS-CoV-2 infections and the likelihood of seeking treatment or medical care during different waves of the pandemic. Methods: The NC-CCRP is a longitudinal observational study of 37, 820 participants who completed a daily symptom log from April 2020 through February 2022, during which there were 5, 167 self-reported COVID-19 infections. Three variant periods were defined as pre-delta, delta, and omicron, based on the predominant variant in North Carolina. Quasi-Poisson and logistic regression models adjusted for demographics and vaccination were used to assess COVID-19 symptoms and their duration and seeking treatment or hospitalization. Results: Cough was the most reported symptom in all waves and increased from 77% pre-delta to 85% during omicron (p=0.001). Sore throat was more common during self-reported infections during omicron (71%), compared with 62% during delta and 54% pre-delta (p< 0.001). The largest change in proportion reporting a symptom was loss of taste or smell which decreased from 55% during pre-delta to 17% during omicron (p< 0.001). Compared with the pre-delta period, delta (incidence risk reduction, IRR 0.86; 95% CI 0.79-0.93) and omicron (IRR 0.67; 95% CI 0.61-0.73) were associated with lower symptom duration. Participants infected during the delta wave were more likely to seek treatment compared with either pre-delta (odds ratio, OR 1.32 95% CI 1.06-1.64) or omicron (OR 1.42; 95% CI 1.21-1.67). Omicron period infections were associated with a lower likelihood of self-reported hospitalization compared with pre-delta (OR 0.26; 95% CI 0.10-0.59) or delta (OR 0.26; 95% CI 0.11-0.60). Vaccination was associated with a reduced likelihood of hospitalization (OR 0.35; 95% CI 0.18-0.70). Proportion and Duration of Symptoms by Variant Wave; Unadjusted by Vaccination Status. Conclusion: Our study indicates evolution in symptom presentation and duration by variant period. The omicron wave was associated with shorter duration and lower severity of illness. Longitudinal tracking of symptomology and severity of a novel pathogen provide insights into the evolution of the pathogen in the community and is vital for public health and clinical response. Disclosures: All Authors : No reported disclosures.